2022
DOI: 10.1021/acs.langmuir.2c02693
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Removal of Lead/Cadmium by Phosphoric Acid-Modified Hydrochar Prepared from Fresh Banana Peels: Adsorption Mechanisms and Environmental Application

Abstract: In this work, a phosphoric acid (H3PO4)-modified hydrochar (BPH200) was prepared at a low temperature (200 °C) in an air atmosphere with fresh banana peels as the raw material. The Cd2+ and Pb2+ adsorption behaviors and mechanisms of BPH200 were explored. As the temperature rose, co-hydrothermal carbonization of the banana peels and H3PO4 enhanced the transformation of phosphorus (P) species. More orthophosphate and metaphosphate were found in BPH200 than in banana peel hydrochar (BP) without modification. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
(118 reference statements)
0
7
0
Order By: Relevance
“…Previous studies have showed that H 3 PO 4 modification for biochars enhanced the SSA by generation of micropores, while H 2 O 2 increased the content of oxygen-containing groups, particularly carboxyl groups. , It was found that the carbonization degree of modified HCs with 50% wt H 3 PO 4 was the highest, and the hydroxyl and carboxyl functional groups formed on the surface of HCs modified by 30% wt H 3 PO 4 . Other researchers indicated that H 3 PO 4 promoted the hydrolysis of lignin, cellulose, and hemicellulose existing in the cell walls of biomass through the processes of dehydration, condensation, polymerization, and aromatization. , Moreover, the mesopores of HCs modified by H 3 PO 4 increased, resulting in the large SSA. , In addition, the carbon content of 20% H 2 O 2 -modified HCs decreased from 71 to 61%, and the oxygen content increased from 20 to 30%. The content of carboxylic, lactone, and phenolic hydroxyl functional groups increased by 3.4, 2.1, and 2.0 times, respectively .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have showed that H 3 PO 4 modification for biochars enhanced the SSA by generation of micropores, while H 2 O 2 increased the content of oxygen-containing groups, particularly carboxyl groups. , It was found that the carbonization degree of modified HCs with 50% wt H 3 PO 4 was the highest, and the hydroxyl and carboxyl functional groups formed on the surface of HCs modified by 30% wt H 3 PO 4 . Other researchers indicated that H 3 PO 4 promoted the hydrolysis of lignin, cellulose, and hemicellulose existing in the cell walls of biomass through the processes of dehydration, condensation, polymerization, and aromatization. , Moreover, the mesopores of HCs modified by H 3 PO 4 increased, resulting in the large SSA. , In addition, the carbon content of 20% H 2 O 2 -modified HCs decreased from 71 to 61%, and the oxygen content increased from 20 to 30%. The content of carboxylic, lactone, and phenolic hydroxyl functional groups increased by 3.4, 2.1, and 2.0 times, respectively .…”
Section: Introductionmentioning
confidence: 95%
“…20,23 Moreover, the mesopores of HCs modified by H 3 PO 4 increased, resulting in the large SSA. 24,25 In addition, the carbon content of 20% H 2 O 2 -modified HCs decreased from 71 to 61%, and the oxygen content increased from 20 to 30%. The content of carboxylic, lactone, and phenolic hydroxyl functional groups increased by 3.4, 2.1, and 2.0 times, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The flourishing literature has reviewed the advanced, non-energy applications of hydrochars from disparate waste biomass. HTC of lignocellulosic materials, an environmentally benign process, yields a carbonaceous solid likely to undergo further transformation to functional matrices that can be applied to green, sustainable industrial processes of catalysis, electrical energy storage, and adsorption . Accordingly, HC recently came to the attention of researchers dealing with superperforming, hybrid materials. , Innovative adsorption processes make up a vast area for HC applicability because the carbonaceous matrix allows for surface modification in situ , i.e., during the HTC reactions , and postreaction. , Gas-phase separations exploit the affinity of hydrochar for acidic compounds. The literature primarily focuses on capturing CO 2 in the HC matrix, which is understandable considering the environmental relevance of this specific topic.…”
Section: Introductionmentioning
confidence: 99%
“…17 Accordingly, HC recently came to the attention of researchers dealing with superperforming, hybrid materials. 14,18−20 Innovative adsorption processes make up a vast area for HC applicability because the carbonaceous matrix allows for surface modification in situ, i.e., during the HTC reactions 21,22 and postreaction. 23,24 Gas-phase separations exploit the affinity of hydrochar for acidic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In many previous studies, biochar has shown great potential for heavy metal wastewater treatment. Previously, biochar prepared from banana peels (Ge et al 2022), maize straw (Hu et al 2022b), eucalyptus leaves (Dai et al 2021), banana straw (Deng et al 2020), wheat straw (Qi et al 2023) and other raw materials has been used to treat heavy metal-containing wastewater with good adsorption effects, indicating that agricultural and forestry waste is good biochar raw material. China is the country with the most plentiful bamboo resources, but the levels of bamboo processing and utilization are low (Dlamini et al 2022).…”
Section: Introductionmentioning
confidence: 99%